Hubungan Self Image dengan Flexing Behaviour pada Gen Z Pengguna Instagram di ITSK RS dr. Soepraoen - Permatasari, Dian; Priasmoro, Dian Pitaloka; Murtadho, Maulana Arif (Jurnal Keperawatan Muhammadiyah, 2024)
Flexing behaviour can occur for a variety of reasons, one of which is to visualize self image because one needs a recognition, self-esteem and a need for social life. The study aims to identify the relationship between self image and flexing behaviour among Gen Z Instagram users at the ITSK RS dr. Soepraoen. This research uses a quantitative research design with a cross sectional approach. The population was 177 college students with a sample of 135 college students. The technique used is accidental sampling. The research was conducted from 14 to 28 February 2024. The research instrument uses a questionnaire in the form of a google form. Data analysis using univariate and bivariate analysis. The results were tested using spearman rho. Obtained sig (2-tailed) p value = 0,000 < 0.05 indicates that H₁ received which means there is a relationship between self image with flexing behaviour among Gen Z Instagram users at ITSK RS dr. Soepraoen. The results of the study had a correlation coefficient (r) of 0.300 included in the study with a moderate strength of the relationship and with a positive direction which means the higher self image make it the lower flexing behaviour. The results of this research expect the participation of institutions to be able to provide education related to the need of students to improve their self image by attending academic and non-academic activities on campus. Keywords: Self Image, Flexing Behaviour, Gen Z, Instagram.